Study Of Corrosion And Engine Performance Characteristics Of Emulsified Diesel - Siva Sankara Arudra, Siva (Universiti Teknologi Petronas, 2010)

(untitled)
Oil plays a vital role in world growth in every sector. Oil consumption is targeted to increase tremendously in upcoming years. The highest occupied fuel currently is the diesel fuel as this fuel is widely applied in vast sectors around the world. However, there are many studies and researches that prove that diesel fuel is the major contributor to world air pollution. This is due to the particulate matter and harmful gases emission by the diesel fuel when burning process. Hence, to overcome this problem, world bodies or organizations have come out with many solutions to substitute world diesel usage. One of the most potential solutions is the emulsified diesel fuel. This emulsified diesel fuel is produced by emulsifying bio-oil and diesel fuel. But, this bio-oil emulsified diesel fuel is claimed to have few drawbacks in sense of corrosiveness and engine performance. Hence, this project is established to study the corrosion and engine performance of B10 and B20 emulsified diesel fuel. The objectives of this project are to check the corrosion rate of this bio-oil emulsified diesel fuel under the influence of temperature and time interval. This corrosion study will be conducted only on stainless steel and mild steel material. Besides that, this project also aims to study and investigate the engine performance of this fuel in aspects of specific fuel consumption (SFC), torque and engine power. For corrosion test, immersion and SEM test method used, while for engine performance, test bed engine method used to test the fuels. The outcome from the corrosion test shows that B10 and B20 emulsified fuels are more corrosive than diesel fuel. The results also prove that higher temperature will lead to higher corrosion rate. While for engine performance, B10 and B20 emulsified fuel has similar torque and engine power with diesel fuel, but these emulsified fuels has slightly higher specific fuel consumption (SFC) compare to diesel fuel.In whole, this project is a success as all objectives set are met and the outcomes obtained resolve most of the issues or enquiries about emulsified else.